Target profiling of an antimetastatic RAPTA agent by chemical proteomics: relevance to the mode of action. Issue 4 (18th February 2015) - Babak, Maria V.; Meier, Samuel M.; Huber, Kilian V. M.; Reynisson, Jóhannes; Legin, Anton A.; Jakupec, Michael A.; Roller, Alexander; Stukalov, Alexey; Gridling, Manuela; Bennett, Keiryn L.; Colinge, Jacques; Berger, Walter; et al.
Abstract : The RAPTA pharmacophore was linked to beads to identify its biomolecular targets in cancer cells. Abstract : The clinical development of anticancer metallodrugs is often hindered by the elusive nature of their molecular targets. To identify the molecular targets of an antimetastatic ruthenium organometallic complex based on 1, 3, 5-triaza-7-phosphaadamantane (RAPTA), we employed a chemical proteomic approach. The approach combines the design of an affinity probe featuring the pharmacophore with mass-spectrometry-based analysis of interacting proteins found in cancer cell lysates. The comparison of data sets obtained for cell lysates from cancer cells before and after treatment with a competitive binder suggests that RAPTA interacts with a number of cancer-related proteins, which may be responsible for the antiangiogenic and antimetastatic activity of RAPTA complexes. Notably, the proteins identified include the cytokines midkine, pleiotrophin and fibroblast growth factor-binding protein 3. We also detected guanine nucleotide-binding protein-like 3 and FAM32A, which is in line with the hypothesis that the antiproliferative activity of RAPTA compounds is due to induction of a G2 /M arrest and histone proteins identified earlier as potential targets.